Re-Membering Our Nations: Indigenous Custom Adoption and Determining Belonging Beyond the Indian Act - Wilson, Ariane (Arts, 2022)
This is a study and analysis of Indigenous membership and belonging. Specifically, this thesis takes up the historical and contemporary harms of colonialism and the Indian Act (1876) have had on First Nations band membership codes and Indigenous practices of determining belonging. The central task of this study is to determine how Indigenous nations can determine membership and belonging beyond colonial confines. I draw on literature on Indigenous nationhood and peoplehood to develop a framework that outlines pathways for belonging that are embedded within networks of kinship and relationality, rather than the arbitrary boundaries of colonial legislation. Throughout the thesis, I argue that Indigenous custom adoptions, in the way they occur within Indigenous legal, political, and kinship systems, are inherently acts of self-determination and as such, provide insight into how Indigenous nations can move beyond the Indian Act.